Real Wage Cyclicality in the Eurozone Before and During the Great Recession: Evidence from Micro Data - Gregory Verdugo (Institute for the Study of Labor (IZA), 2015)
We study the response of real wages to the business cycle in eight major Eurozone countries before and during the Great Recession. Average real wages are found to be acyclical, but this reflects, in large part, the effect of changes in the composition of the labour force related to unemployment variations over the cycle. Using longitudinal micro data from the ECHP and SILC panels to control for composition effects, we estimate the elasticities of real wage growth to unemployment increases between -0.6 and -1 over the period 1994-2011. Composition effects have been particularly large since 2008, and they explain most of the stagnation or increase in the average wage observed in some countries from 2008 to 2011. In contrast, at a constant labour force composition in terms of education and experience, the figures indicate a significant decrease in average wages during the downturn, particularly in countries most affected by the crisis. Overall, there is no evidence of downward nominal wage rigidity during the Great recession in most countries in our sample.
Keywords: J30; E32; 330; wage cyclicality; wage rigidity; Great Recession; Eurozone